KILKA SŁÓW O AKSJOLOGII PRAWA KONKURENCJI A PRAWA PATENTOWEGO: ABSOLUTNA OCHRONA PATENTOWA WYNALAZKÓW BIOTECHNOLOGICZNYCH - Uchańska, Joanna (Zeszyty Prawnicze, 2016)
A FEW REMARKS ON THE AXIOLOGY OF COMPETITION LAW AND PATENT LAW: THE ABSOLUTE PATENT PROTECTION OF BIOTECHNOLOGICAL INVENTIONS Summary This paper discusses the important issue of the dependence of patent law on competition law, and their relations. The author carries out a comprehensive analysis of the axiomatic foundations of these two systems. She starts by putting a hypothesis that patent law and competition law are complementary. Both are a remedy for the shortcomings of the market, each in a different, but complementary way acting as tools in a mechanism to stimulate innovation. Subsequently, the paper presents the patent protection of biotechnological inventions, in particular its sensitive aspect, namely the absolute protection of biotechnological inventions. Hence she goes on to discuss various standpoints on the patent protection of biotechnological inventions. In the final part of the article she presents the well-nigh inevitable clash between the absolute protection of biotechnological inventions and the law on protection of competition. The article also shows that competition law is in conflict with the axiological foundations of patent protection, in prejudice to the principle that patent protection is a system envisaged for the benefit of society as a whole and should be established and performed using the principle of proportionality.